FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELENGKAPAN DOKUMENTASI PENGKAJIAN RAWAT JALAN DI RUMAH SAKIT AWAL BROS BATAM TAHUN 2016 - Agus Salim (Journal of Hospital Administration and Management, 2020)
Documentation  is as a communication tool where documentation in providing nursing care will be coordinated to avoid or prevent repetitive information. Documentation as a mechanism of accountability which contains documentation standard rules or provisions on the implementation of documentation, therefore the quality of the documentation truth will easily be justified and can be used as a protector of the lawsuit because it has a legal standard. Document as individual nursing care facilities, as a means of evaluation, and as a means to enhance cooperation between the health care team. This study aims to determine the factors that related to the documentation  completeness. This type of research is descriptive analytic approach of Cross Sectional study. Sampling using total sampling technique. Respondents in this study were 51 people. Data retrieved by distributing questionnaires and observasi, there was significant relationship between motivation and completeness of documentation with the value (p = 0.002). There is a significant relationship workloads with complete documentation with a value (p = 0.039). there is a significant relationship between supervision with the completeness of the documentation with the value (p = 0.003). It can be concluded that the completeness of the documentation associated with motivation, workload and supervision. Agencies are expected to hospital in order to improve the support and teaching to nurses in order to obtain complete documentation, and for further research in order to add a variable that supports the completeness of the documentation